Patient-centred Communication Discourse of In-home Medical Consultations for Older Adults - Kondo, Kayo (Language at Work, 2022)
This book presents a comprehensive analysis of the use of patient-/person-centred communication in providing health care for ageing populations through an ethnographic approach to physician in-home medical consultations in Tokyo, Japan, alongside interviews with physicians